Urgensi Kepemimpinan Yang Unggul Dalam Peningkatan Mutu Pendidikan - Rubi Babullah; Istikhori Istikhori; Neneng Neneng; Ujang Natadireja; Siti Nurafifah (Lembaga Pengembangan Kinerja Dosen, 2024)
This research discusses the urgency of superior leadership in the context of improving the quality of education. With a focus on the role of leadership at the school level, this study aims to investigate how effective leadership practices can shape a supportive school culture, improve the quality of teaching and learning, and result in better academic achievement. Data was collected through interviews with school principals, teachers and school staff from various educational backgrounds, as well as literature study. Analysis was carried out to identify superior leadership practices, including clear vision, the ability to motivate and lead a team, and the ability to adapt to changes occurring in the educational environment. The research results show that superior leadership has a significant impact in improving the quality of education. Visionary and inclusive leadership practices help create a dynamic learning environment and stimulate student growth. Apart from that, leadership that is able to develop and empower school staff also contributes to improving the quality of teaching and learning in schools. This research provides an in-depth understanding of the importance of superior leadership in achieving quality education goals. The practical implications of these findings can be used to develop leadership training programs, design effective education policies, and strengthen collaboration between schools, government and society in supporting overall improvement in the quality of education.